Assessment of first derivative of doppler blood flow velocity in vascular aging - Zulaika, H.; Noor Azmi, Azran Azhim; Saleh, M.; Baghepour, P.; Kinouchi, Y.; Ibrahim, F. (2014)
The aim of this study is to determine the first derivative of blood flow velocity (FDBFV) in common carotid artery (CCA) in order to evaluate cardiovascular functions. The extracted derivative of the velocity is suggested the acceleration waves which able to provide an aging index (AGI) in the cardiovascular system. In the study, acceleration wave derived from FDBFV consist of a, b, c, d, e and f waves which represent the initial positive, early negative, re-increasing, late re-decreasing, diastolic positive waves and diastolic negative waves, respectively. The FDBFV waveforms of 227 healthy volunteers are statistically analyzed in the study. Pearson’s correlation analysis is used to determine the relationship between all variables and factors on the selected hemodynamic data. In the study, there are significant difference (r=0.727, p<0.001) of AGI in FDBFV. We found that f wave in FDBFV waveform shows strong correlation (p< 0.001) to blood pressure. In conclusion, the potential of FDBFV in CCA is an effective method to evaluate the vascular aging.